Application of Environmental Justice Analysis in a Statewide Freight Plan. Issue 1 (2017) - Ryan, Christopher
Executive Order 12898 and subsequent U.S. Department of Transportation (DOT) orders require all state DOTs to complete environmental justice analyses to identify disproportionately high and adverse effects of programs, polices, and activities on minority populations and low-income populations. Many analysis techniques have emerged in practice and academic literature, but no official guidance has designated a preferred analysis approach. The passage of the Fixing America's Surface Transportation Act introduced a number of new freight provisions for state DOTs, including a requirement to develop state freight plans to be eligible for funding through the National Highway Freight Program. This paper reviews the existing guidance for environmental justice analyses and documents the application of this guidance to an environmental justice analysis for the Minnesota Statewide Freight System Plan. The plan provides strategies and a policy framework for statewide freight stakeholders to guide planning efforts and investments in the state freight system. The paper concludes with a discussion of further considerations, strategies, and challenges facing freight planning practitioners in future freight environmental justice analyses.